The benefit of MR‐only radiotherapy treatment planning for anal and rectal cancers: A planning study. Issue 11 (22nd October 2021) - Bird, David; Nix, Michael G.; McCallum, Hazel; Teo, Mark; Gilbert, Alexandra; Casanova, Nathalie; Cooper, Rachel; Buckley, David L.; Sebag‐Montefiore, David; Speight, Richard; Al‐Qaisieh, Bashar; Henry, Ann M.
Abstract: Introduction: Limited evidence exists showing the benefit of magnetic resonance (MR)‐only radiotherapy treatment planning for anal and rectal cancers. This study aims to assess the impact of MR‐only planning on target volumes (TVs) and treatment plan doses to organs at risks (OARs) for anal and rectal cancers versus a computed tomography (CT)‐only pathway. Materials and methods: Forty‐six patients (29 rectum and 17 anus) undergoing preoperative or radical external beam radiotherapy received CT and T2 MR simulation. TV and OARs were delineated on CT and MR, and volumetric arc therapy treatment plans were optimized independently (53.2 Gy/28 fractions for anus, 45 Gy/25 fractions for rectum). Further treatment plans assessed gross tumor volume (GTV) dose escalation. Differences in TV volumes and OAR doses, in terms of Vx Gy (organ volume (%) receiving x dose (Gy)), were assessed. Results: MR GTV and primary planning TV (PTV) volumes systematically reduced by 13 cc and 98 cc (anus) and 44 cc and 109 cc (rectum) respectively compared to CT volumes. Statistically significant OAR dose reductions versus CT were found for bladder and uterus (rectum) and bladder, penile bulb, and genitalia (anus). With GTV boosting, statistically significant dose reductions were found for sigmoid, small bowel, vagina, and penile bulb (rectum) and vagina (anus). Conclusion: Our findings provide evidence that the introduction of MR (whether through MR‐only or CT‐MR pathways) to radiotherapy treatment planning for anal and rectal cancers has the potential to improve treatments. MR‐related OAR dose reductions may translate into less treatment‐related toxicity for patients or greater ability to dose escalate.